2022
DOI: 10.3390/rs14174189
|View full text |Cite
|
Sign up to set email alerts
|

Asian Rice Calendar Dynamics Detected by Remote Sensing and Their Climate Drivers

Abstract: Detecting crop calendar changes is critically important for crop monitoring and management, but the lack of annual, Asia-wide, and long-term rice calendar datasets limits our understanding of rice phenological changes and their climate drivers. In this study, we retrieved key rice phenological dates from the GLASS AVHRR LAI through combining threshold-based and inflection-based detection methods, analyzed the changes during the period 1995–2015, and identified the key climate drivers of the main rice seasons i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Yang et al [16] and Qiu et al [17] identified different driving patterns of vegetation climate under various altitude gradients of the Qinghai-Tibet Plateau, and vegetation growth in relatively high-altitude areas is determined by growing season precipitation and atmospheric CO 2 concentrations, while relatively low altitudes are dominated by growing precipitation. Climate change has a profound impact on vegetation dynamics, hydrological cycles, and ecosystem productivity globally [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al [16] and Qiu et al [17] identified different driving patterns of vegetation climate under various altitude gradients of the Qinghai-Tibet Plateau, and vegetation growth in relatively high-altitude areas is determined by growing season precipitation and atmospheric CO 2 concentrations, while relatively low altitudes are dominated by growing precipitation. Climate change has a profound impact on vegetation dynamics, hydrological cycles, and ecosystem productivity globally [18,19].…”
Section: Introductionmentioning
confidence: 99%